TEACHING TECHNIQUE OF WRITING USING NATURAL ENVIRONMENT: A CASE STUDY OF THE EIGHT GRADE STUDENTS OF JUNIOR HIGH SCHOOL IN SEKOLAH ALAM AR-RIDHO TEMBALANG SEMARANG - Festi Himatu Karima; Hesti Utami (Universitas PGRI Semarang, 2013)
This study aims at observing the benefit and the teaching technic of teaching writitng at Sekolaha alam Ar Ridho seamrang. This is a nature based school in which emphasis the teaching learning process basis of nature.Based on the case we need a school which has goals to prepare students who have good attitude, faithful, and knowledge. The writer wants to know the benefits and technique of teaching using natural environment in “Sekolah Alam Ar-Rhido” Tembalang, especially for teach writing skill. This study focuses on the examining three main problems; the technique of teaching writing in Sekolah Alam Ar-Ridho; the effectiveness of Teaching Writing in the natural environment ; the problems faced by the teacher and students in teaching learning process in the natural environment and how the teacher solve the problem.The writer wants to know the benefits and technique of teaching using natural environment in “Sekolah Alam Ar-Rhido” Tembalang, especially for teachwriting skill. This study focuses on the examining three main problems;The technique of teaching writing in Sekolah Alam Ar-Ridho; the effectiveness of Teaching Writing in the natural environment ; the problems faced by the teacher and students in teaching learning process in the natural environment and how the teacher solve the problem